Effects of a novel rice-based diabetes-specific formula on postprandial glucose and gastrointestinal hormones: a double-blinded multi-arm randomized crossover trial - Chaiyakul, Supat; Ketkham, Narong; Chaichana, Chartchai; Khumkhana, Nanta; Deekum, Wanjan; Wongshaya, Pakwuan; Suwanmalai, Thaniya; Hutchinson, Carol; Pramyothin, Pornpoj (Frontiers in Endocrinology, 2023)
Introduction We developed a novel rice-based medical food for diabetes (MFDM) powder formula, using locally available ingredients in Thailand, which can potentially improve patient access to diabetes-specific formula (DSF) by reducing cost and improving availability. Purpose The goals of our studies were to 1) measure the glycemic index (GI) and glycemic load (GL) of the MFDM powder formula in healthy individuals, and 2) assess postprandial glucose, insulin, satiety, hunger, and gastrointestinal (GI) hormone responses in adults with prediabetes or early type 2 diabetes after consuming MFDM in comparison with a commercially available standard formula (SF) and a DSF. Methods In Study 1, glycemic responses were assessed using the area under the curve (AUC), which was used to calculate GI and GL. Study 2 was a double-blinded multi-arm randomized crossover trial enrolling participants with either prediabetes or type 2 diabetes of ≤6 years. At each study visit, participants consumed either MFDM, SF, or DSF which contained 25 g of carbohydrates. Hunger and satiety were assessed using a visual analog scale (VAS). Glucose, insulin, and GI hormones were assessed using AUC. Results All participants tolerated the MFDM well with no adverse events. In Study 1, the measured GI was 39 ± 6 (low GI) and GL was 11 ± 2 (medium GL). In Study 2, glucose and insulin responses were significantly lower after MFDM compared with SF (p-value<0.01 for both), however, those responses were similar between MFDM and DSF. MFDM suppressed hunger, promoted satiety, stimulated active GLP-1, GIP, and PYY, and suppressed active ghrelin although these changes were similar to SF and DSF. Conclusions MFDM had a low GI and a low-to-medium GL. In people with prediabetes or early type 2 diabetes, MFDM elicited reduced glucose and insulin responses when compared with SF. Rice-based MFDM may be an option for patients who are at risk for postprandial hyperglycemia. Clinical Trial Registration https://www.thaiclinicaltrials.org/show/TCTR20210731001, identifier TCTR20210731001; https://www.thaiclinicaltrials.org/show/TCTR20210730007, identifier TCTR20210730007.